Estrategias metodológicas para mejorar el rendimiento académico en la asignatura de Matemática de los estudiantes de primer ciclo de la Universidad Técnica de Cotopaxi extensión La Maná, durante el ciclo académico Octubre 2010 a Febrero 2011. - Reyes Vallejo, Elvia Marlene (2011)
With this investigation is sought to end up improving the learning of the university students by means of the use of methodological strategies The same ones that designed for the teaching processes and learning they produce changes in the mental outlines and the cognitive structures of the students, for the development of the logical thought. It is based on the analysis of the methodological factors of the academic yield of the students of First Cycle of the Technical University of Cotopaxi Extension “The Manna; The work begins with a detailed description about the complexity of the teaching of mathematics, it is considered some didactic principles that characterize to the university mathematical education and later on the methodological strategies used for this discipline is analyzed. The investigation is descriptive not experimental, through the induction, deduction and the analysis and synthesis, under a qualitative perspective. The data were gathered through class observations and surveys, to the students and educational of the University. The theoretical sustenances and of field approached study presently, through the analysis and interpretation and of different authors' gathered considerations, they allowed to base some aspects and points of view on the methodological strategies that are adjusted to the didactic and pedagogic principles for the appropriate development of the teaching process and learning of the mathematics in the superior level.